The Spirit of Japanese Law - Kenneth L. Port (Washington University Global Studies Law Review, 2002)
In this book review, Kenneth L. Port offers a review of Dr. John Owen Haley's book, The Spirit of Japanese Law.
Keywords: The Spirit of Japanese Law; John Owen Haley; Japan; Legal history